Manajemen Ekonomi Syariah dalam Fungsi-Fungsi Bisnis Islam - Nani Feliyani (JES (Jurnal Ekonomi Syariah), 2021)
Abstract: In sharia business, management is used as a basic element that is attached to business processes that will be used as a reference by managers in carrying out activities to achieve goals. The management urgency in business is designed to cover four functions, namely production, personnel, marketing and finance. Business in Islam also aims to achieve four main things: targets results, material and non-material benefits, sustainability of growth, and blessings. This research is qualitative library research using sources from various references conducted descriptively and analytically. The findings suggest that in its application, business management cannot be separated from the beliefs and values underliying it, which must be in accordance with the view of life and Islam. Keywords: management; Islamic business; transactions